2018
DOI: 10.1007/s40097-018-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of physicochemical parameters in the biofabrication of gold nanoparticles using marine macroalgae Padina tetrastromatica and its catalytic efficacy in the degradation of organic dyes

Abstract: Green synthesis of metallic nanoparticles by means of renewable bioresources has emerged as a new trend in current nanotechnology research with improved environmental safety. In the current study, monodispersed gold nanoparticles (AuNPs) with excellent stability were prepared in a completely green and cost effective manner using aqueous extract of marine macroalgae-Padina tetrastromatica. The influence of reaction conditions such as the quantity of seaweed extract, temperature, precursor metal ion concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…A further rise in the HAuCl 4 concentration resulted in a shift to a longer wavelength owing to the rise in particle size. Such findings were consistent with prior investigations conducted by Bankar et al [ 16 ] and Princy et al [ 34 ] where it was confirmed that 1.0 mM HAuCl 4 was found to be the best for the synthesis of AuNPs. Similarly, among the different volumes of P. alata extract tested, synthesis using 1.0 ml of the extract showed increased production of AuNPs with an intensity absorbance peak at 530 nm.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A further rise in the HAuCl 4 concentration resulted in a shift to a longer wavelength owing to the rise in particle size. Such findings were consistent with prior investigations conducted by Bankar et al [ 16 ] and Princy et al [ 34 ] where it was confirmed that 1.0 mM HAuCl 4 was found to be the best for the synthesis of AuNPs. Similarly, among the different volumes of P. alata extract tested, synthesis using 1.0 ml of the extract showed increased production of AuNPs with an intensity absorbance peak at 530 nm.…”
Section: Resultssupporting
confidence: 93%
“…The UV-Vis spectra ( Figure 2) depicted strong intense SPR peaks for Ah-AuNPs (534.4 nm), Li-AuNPs (537.6 nm), Mc-AuNPs (538.4 nm), Cl-AuNPs (548.3 nm), Pa-AuNPs (529.6 nm), and Vi-AuNPs (531.5 nm). Similar observations of apparent color change from pale yellow to pink, [34] ruby red, [23] and violet [35] with the peak absorptions between 525 and 550 nm have been recorded, suggesting the formation of AuNPs. Therefore, the six synthesized AuNPs alone chosen for further screening study of antioxidant activity.…”
Section: Phytosynthesis Of Aunpssupporting
confidence: 83%
“…6 Advances in NP synthesis and increased use of these particles in many fields have led researchers to evaluate mechanisms to improve the biocompatibility of NPs. 7,8 In addition, increased use of NPs has resulted in interest in the development of green approaches for the fabrication of NPs. Biological synthesis has several advantages including reduced production of toxic by-products, improved stability, and reduced toxicity against healthy cells.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were performed by varying one factor at a time by keeping other factors at a fixed value. Surface plasmon resonance (SPR) Peak was recorded at 530 nm as it is evident from literature reports that blue shift is seen due to decrease in particle size owing to monodispersed nature of nanoparticles [17]. Similarly, experiments were performed by varying other factors and keeping previously varied factors at the optimized values.…”
Section: Selection Of Levels Of Parameters By Ofatmentioning
confidence: 99%